PERENCANAAN DESAIN TEMPAT PENYIMPANAN SEMENTARA (TPS) LIMBAH B3 TEMPAT PEMROSESAN AKHIR (TPA) PT. X: PERENCANAAN DESAIN TEMPAT PENYIMPANAN SEMENTARA (TPS) LIMBAH B3 TEMPAT PEMROSESAN AKHIR (TPA) PT. X - Wazna Auvaria, Shinfi; Muhammad Andi , Ramadhan; rhenny, ratnawati (Jurnal Teknologi Lingkungan, 2025)
Hazardous Waste Management at PT. X is focused on the design of a Temporary Storage Facility (TSF) that complies with technical standards and regulatory requirements. The types of hazardous waste identified include used oil, used rags, grease, and hazardous waste packaging, all of which require special handling to prevent adverse impacts on human health and the environment. The objective of this study is to design a hazardous waste TPS at PT. X. The planning method refers to the Regulation of the Minister of Environment and Forestry (Permen LHK) No. 6 of 2021. Data were collected through interviews, observations, and logbook analysis to determine the characteristics, quantities, and sources of hazardous waste generation. Based on these data, a TPS design was developed with supporting facilities such as ventilation, fire extinguishers, first aid kits, and specific labeling according to waste characteristics. Hazardous waste is stored for a maximum of 90 days before being transported by an authorized third party, ensuring structured and environmentally sound management. The proposed TPS design measures 3 × 2 × 3 meters and is equipped with safety facilities, including ventilation, fire extinguishers, first aid kits, and labeling in accordance with waste characteristics. This design complies with regulations on maximum storage duration before transfer to a licensed third party. Therefore, the results of this study provide a TPS design that is not only spatially efficient but also ensures regulatory compliance, enhances occupational safety, and minimizes the potential risk of environmental pollution.